Financing for Islamic Higher Education (A Case Study in STIT Al-Ittihadiyah Labuhanbatu Utara) - Amiruddin Siahaan; Dedi Sahputra Napitupulu; Zulkipli Nasution (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This research aims to investigate the Islamic higher education finance structure, particularly in terms of the source of money and their usage. This research used a qualitative approach that employed a case study with data collecting techniques such as interviews, observations, and document studies. Informants in this research were chairman of Al-Ittihadiyah North Sumatra, the chairman of the Al-Ittihadiyah Education Foundation in Labuhanbatu Utara, the chairman of STIT AILU, the treasurer of STIT AILU, and students. While the analysis of this research data used data collection techniques, data presentation, reduction, and verification. According to the findings of this study, STIT AILU received educational support from the Al-Ittihadiyah organization in North Sumatra, local governments, student tuition payments, and the waqf movement. Meanwhile, education funds were allocated for campus management and infrastructure completion. Additionally, funds were utilized to improve the quality of Human Resources (HR) by providing further education scholarships to permanent professors and different academic events such as seminars and conferences.